A cement-based copper tailings geopolymer and methods of use thereof

CN122771691APending Publication Date: 2026-09-18谢军 +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611052002.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0004]然而,现有技术存在诸多缺陷,难以适配高硅铝低钙型铜尾矿处置,主要缺点如下:(1)水泥消耗大、成本高、碳排放高

Benefits of technology

(1)本发明采用粒化高炉矿渣微粉、钢渣微粉等工业固废作为复合活性激发剂,可替代40%~60%的硅酸盐水泥,大幅减少水泥用量,既降低胶凝材料的制备成本,又可减少水泥生产带来的碳排放,契合绿色低碳、减污降碳的环保要求;同时本发明充分利用磷石膏、脱硫石膏等工业副产品,可实现多类固废协同消纳,进一步提升资源化利用效益,降低固废的整体处置成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the technical field of filling cementitious materials, and particularly relates to a cement-based copper tailings sand cementitious material and a use method thereof. The cement-based copper tailings sand cementitious material is prepared from the following raw materials by weight: cementitious main material, active activator, chemical stabilizer, alkalinity regulator, functional additive and water. The present application can achieve high cement replacement rate, 28-day unconfined compressive strength of the solidified body of more than 4.0 MPa, heavy metal fixation efficiency of more than 99%, and excellent performance, while having the characteristics of low cost, low carbon emission, simple process and wide adaptability, and can be used for large-scale disposal of copper tailings, solving the problems of pollution and safety hazards caused by stacking, and being suitable for various copper tailings filling and solidification, mine ecological restoration and large-scale solid waste resource utilization scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of filling cementitious materials, specifically relating to a cement-based copper tailings sand cementitious material and its application method. Background Technology

[0002] Copper is an important mineral resource in my country. The copper tailings produced during mining and beneficiation have a massive stockpile and low utilization rate (over 360 million tons were produced in 2023, with a utilization rate of only 30.13%). Large quantities of tailings occupy land, pose a risk of dam collapse, and contain copper... 2+ Pb 2+ Heavy metals are easily leached and pollute water and soil, threatening the ecology and human health. Their large-scale harmless disposal and resource utilization are the key to the sustainable development of mines.

[0003] The main pathways for the resource utilization of copper tailings include the recovery of valuable metals and the preparation of building materials. Among these, cement-based cementitious material solidification technology is an effective path for large-scale disposal. By generating CSH gel cementitious tailings particles through cement hydration, heavy metal stabilization can be achieved, meeting engineering and environmental protection requirements.

[0004] However, the existing technology has many defects and is difficult to adapt to the disposal of high-silicon-aluminum-low-calcium copper tailings. The main disadvantages are as follows: (1) High cement consumption, high cost and high carbon emissions. The cement content of the existing technology needs to reach more than 10%-20% of the dry weight of the tailings, which increases the cost and does not meet the goals of green and low-carbon and solid waste "pollution reduction and carbon reduction". (2) Most copper tailings in my country are high-silicon-aluminum-low-calcium. The formation of traditional CSH gel depends on calcium source, resulting in insufficient hydration, low strength of solidified body, high risk of heavy metal leaching, and limited scope of application. (3) The traditional formula is simple, the early shrinkage of solidified body is large and easy to crack, which reduces mechanical and impermeability properties, and the durability of solidified body is insufficient, which aggravates heavy metal leaching and shortens service life. (4) The existing technology regards tailings as inert aggregates, does not activate its potential silica-aluminum cementitious activity, and only achieves passive disposal, which does not meet the direction of efficient utilization of bulk solid waste. (5) Although invention CN119735417A processes ultrafine tailings, it is based on slag powder and has limited ability to adapt to high-silicon, low-aluminum, and low-calcium tailings, making it difficult to fully utilize the activity of tailings.

[0005] Currently, the industrial application of non-ferrous metallurgical slag cementitious materials is limited, with the core bottleneck being the challenge of activating low-activity tailings. Given increasingly stringent environmental regulations, developing inexpensive, efficient, cement-reducing, and widely adaptable preparation technologies has become an urgent need for the industry.

[0006] Based on this, the development of technologies that are suitable for high-silicon, low-alumina, low-calcium copper tailings, require low cement consumption, have strong activation, and have simple processes are of great significance for the resource utilization of copper tailings and the construction of green mines. Summary of the Invention

[0007] Based on the above technical background, the main objective of this invention is to provide a cement-based copper tailings sand cementitious material and its application method, so as to overcome the shortcomings of the prior art.

[0008] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0009] The first aspect of this invention is to provide a cement-based copper tailings sand cementitious material, wherein the cement-based copper tailings sand cementitious material comprises the following raw materials in parts by weight: The main gelling material consists of 70-110 parts by weight, an active activator of 70-190 parts by weight, a chemical stabilizer of 20-45 parts by weight, an alkalinity regulator of 15-35 parts by weight, and functional additives of 1.5-3.0 parts by weight.

[0010] Preferably, the raw materials for preparation further include 15 to 230 parts by weight of water.

[0011] The mass ratio of water to cementitious material (here defined as water-cement ratio) is 0.40 to 0.55.

[0012] Preferably, the cement-based copper tailings sand cementitious material comprises the following raw materials in parts by weight: The mixture contains 80-100 parts by weight of the main gelling material, 80-170 parts by weight of the active activator, 25-40 parts by weight of the chemical stabilizer, 20-30 parts by weight of the alkalinity regulator, 1.8-2.8 parts by weight of the functional additives, and 20-220 parts by weight of water.

[0013] The main cementitious material is silicate cement (PO 42.5).

[0014] The active activator is selected from one or more of granulated blast furnace slag powder (GGBS), steel slag powder, metakaolin, and fly ash.

[0015] Preferably, the active activator is granulated blast furnace slag powder (GGBS) and steel slag powder.

[0016] More preferably, the specific surface area of ​​the granulated blast furnace slag powder is ≥400 m². 2 / kg, with a median particle size D50 of 10 μm to 30 μm.

[0017] More preferably, the specific surface area of ​​the steel slag powder is ≥400 m². 2 / kg, with a median particle size D50 of 15 μm to 25 μm.

[0018] This invention reduces the cost and carbon emissions of cementitious materials by adding active activators (slag, steel slag, etc.) to replace part of the cement (with a replacement rate of 40% to 60%).

[0019] The chemical stabilizer is selected from one or both of phosphogypsum and desulfurized gypsum.

[0020] Preferably, the chemical stabilizer is phosphogypsum or desulfurized gypsum.

[0021] The phosphate and sulfate ions provided by the phosphogypsum and desulfurized gypsum used in this invention can react with heavy metal ions (Cu). 2+ Pb 2 + Zn 2+ (etc.) form insoluble salts, which, combined with physical encapsulation, can significantly reduce the leaching toxicity of heavy metals in copper tailings.

[0022] The alkalinity regulator is quicklime (CaO).

[0023] This invention targets high-silicon-aluminum, low-calcium copper tailings. It utilizes quicklime as an alkalinity regulator to adjust the alkalinity of the cementitious material system, thereby activating the secondary hydration reaction of silicon and aluminum in the active micro powder and copper tailings to generate CSH and CASH gels, which can fully and effectively utilize the potential activity of copper tailings.

[0024] The functional additive is selected from one or both of polycarboxylate superplasticizers and hydroxypropyl methylcellulose ether (HPMC).

[0025] Preferably, the functional additive is a polycarboxylate superplasticizer and hydroxypropyl methylcellulose ether.

[0026] The polycarboxylate superplasticizer and HPMC used in this invention are compounded as functional additives, which can control the fluidity and water retention of the slurry, reduce shrinkage and cracking, and improve the impermeability and long-term stability of copper tailings.

[0027] Preferably, the polycarboxylate superplasticizer is selected from one or more of the following: standard polycarboxylate superplasticizer, early-strength polycarboxylate superplasticizer, and retarded polycarboxylate superplasticizer.

[0028] More preferably, the polycarboxylate superplasticizer is an early-strength polycarboxylate superplasticizer, such as PC-311 type polycarboxylate superplasticizer.

[0029] More preferably, the cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 80 parts by weight of silicate cement, 120 parts by weight of slag powder, 50 parts by weight of steel slag powder, 30 parts by weight of quicklime, 40 parts by weight of phosphogypsum, 2.0 parts by weight of polycarboxylate superplasticizer, 0.5 parts by weight of HPMC (hydroxypropyl methylcellulose ether), and 220 parts by weight of water.

[0030] More preferably, the cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 100 parts by weight of silicate cement, 80 parts by weight of slag powder, 20 parts by weight of quicklime, 30 parts by weight of desulfurized gypsum, 1.5 parts by weight of polycarboxylate superplasticizer, 0.3 parts by weight of HPMC, and 200 parts by weight of water.

[0031] More preferably, the cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 90 parts by weight of silicate cement, 100 parts by weight of slag powder, 30 parts by weight of steel slag powder, 20 parts by weight of quicklime, 25 parts by weight of phosphogypsum, 2.2 parts by weight of polycarboxylate superplasticizer, 0.6 parts by weight of HPMC, and 20 parts by weight of water.

[0032] A second aspect of the present invention is to provide a method of using the cement-based copper tailings sand cementitious material described in the first aspect of the present invention, the method comprising the following steps: Step 1: Crush the copper tailings to obtain copper tailings powder. Mix the copper tailings powder, cementing main material, active activator, alkalinity regulator and chemical stabilizer to obtain copper tailings mixture. Step 2: Add the functional additive to water and mix well to obtain a functional additive solution. Add the functional additive solution to the copper tailings mixture and stir well.

[0033] The steps described above are described in detail below.

[0034] In step 1, the copper tailings are crushed to a particle size of ≤3 mm.

[0035] Preferably, the copper tailings are crushed to a particle size ≤ 2 mm.

[0036] The mixing temperature is 20–30°C, and the mixing time is 2–5 min.

[0037] Preferably, the mixing temperature is 25°C and the mixing time is 3 to 4 minutes.

[0038] In step 2, the stirring temperature is 20–30°C, and the stirring time is 5–8 minutes, until a workable and homogeneous slurry or plastic body is obtained.

[0039] Preferably, the stirring temperature is 25°C and the stirring time is 6-7 minutes.

[0040] For dry copper tailings, they need to be shaped and cured after mixing. For wet copper tailings, they can be directly pumped or cast.

[0041] The well-mixed copper tailings mixture is poured into molds or spread and compacted on-site, and then cured.

[0042] The curing conditions are: 7 to 28 days at a temperature of 20±2℃ and a humidity of ≥95%.

[0043] The beneficial effects of this invention are as follows: (1) This invention uses industrial solid waste such as granulated blast furnace slag powder and steel slag powder as composite active activators, which can replace 40% to 60% of silicate cement, greatly reducing the amount of cement used. This reduces the preparation cost of cementitious materials and the carbon emissions from cement production, meeting the environmental protection requirements of green, low-carbon, pollution reduction and carbon reduction. At the same time, this invention makes full use of industrial by-products such as phosphogypsum and desulfurization gypsum, which can realize the synergistic disposal of multiple types of solid waste, further improving the efficiency of resource utilization and reducing the overall disposal cost of solid waste.

[0044] (2) To address the problems of insufficient calcium source and incomplete hydration in high-silicon-aluminum, low-calcium copper tailings, this invention uses quicklime as an alkalinity regulator to precisely control the alkaline environment of the preparation system. This not only stimulates the secondary hydration reaction of active micro-powders such as slag and steel slag, but also activates the potential cementitious activity of the silicon-aluminum components in the copper tailings themselves, generating a large amount of CSH and CASH hydration gels, which significantly improves the density and mechanical strength of the solidified body. Actual measurements show that the unconfined compressive strength of the solidified body after 28 days can reach over 4.0 MPa, which can fully meet the engineering mechanical requirements for mine filling and roadbed reinforcement, breaking the limitation of traditional technology that only treats tailings as inert aggregates, and achieving efficient utilization of solid waste.

[0045] (3) In this invention, phosphogypsum and desulfurized gypsum are used as chemical stabilizers. The phosphate and sulfate ions released from them can react with Cu in copper tailings. 2+ Pb 2+ Zn 2+ Heavy metal ions such as As undergo complexation and precipitation reactions to form insoluble salts. Combined with the physical encapsulation and adsorption of hydrated gels, a dual stabilization mechanism of "chemical precipitation + physical solidification" is constructed, with a heavy metal fixation efficiency of over 99% and a leaching concentration far below the limit of the "Integrated Wastewater Discharge Standard". This completely solves the ecological hidden dangers of heavy metal leaching pollution of water and soil in tailings and ensures the long-term environmental safety of the solidified body.

[0046] (4) This invention uses polycarboxylate superplasticizer and hydroxypropyl methylcellulose ether (HPMC) as functional additives to precisely control the fluidity, water retention and workability of the slurry, and adapt to different working conditions such as dry tailings and wet tailings with high water content; at the same time, it effectively inhibits early shrinkage and cracking of the solidified body, improves impermeability and structural stability, and reduces the shrinkage rate by more than 30% compared with the traditional cement solidification system, avoids the problem of strength reduction and secondary leaching of heavy metals caused by cracking, extends the service life of the solidified body, and broadens the application scenarios of the technology.

[0047] (5) The raw materials used in this invention are all commercially available conventional materials or industrial by-products, and no special customization is required; the preparation methods described in this invention are all carried out at room temperature, using conventional dry mixing and wet mixing operations, which are fully compatible with traditional concrete and mine filling construction processes, without the need for additional special equipment, and are simple to operate and highly controllable; during the preparation process, the amount and ratio of raw materials can be flexibly adjusted according to the calcium content and moisture content of the tailings, and it is suitable for various types of copper tailings such as high-silicon aluminum low-calcium tailings, medium-calcium tailings, and high-moisture tailings. The threshold for large-scale application is low, and it has extremely strong industrial promotion value. Detailed Implementation

[0048] The present invention will now be described in detail, and its features and advantages will become clearer and more apparent from these descriptions.

[0049] Example The present invention is further illustrated below with specific examples. These embodiments are merely illustrative and not intended to limit the scope of the invention. All raw materials used in the embodiments of the present invention are commercially available.

[0050] Example 1: Applicable to high-silicon, low-alumina, low-calcium copper tailings. A cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 80 parts by weight of PO 42.5 silicate cement, 120 parts by weight of S95 grade slag powder, 50 parts by weight of steel slag powder, 30 parts by weight of quicklime, 40 parts by weight of phosphogypsum, 2.0 parts by weight of polycarboxylate superplasticizer (PC-311 type polycarboxylate superplasticizer), 0.5 parts by weight of HPMC (hydroxypropyl methylcellulose ether), and 220 parts by weight of water (water-cement ratio = 0.786, where water-cement ratio refers to the ratio of the total mass of water to cement + active powder + quicklime).

[0051] A method for using a cement-based copper tailings sand cementitious material, the method comprising the following steps: Weigh 1000 parts by weight of dry-basis copper tailings (SiO2: 67%, CaO: 0.5%). Dry the weighed dry-basis copper tailings to a moisture content of <5%, then crush them to a particle size of no more than 2 mm. Dry-mix the copper tailings powder, cement, S95 grade slag powder, steel slag powder, quicklime, and phosphogypsum for 4 min (room temperature 25℃) to obtain a dry-mix powder. Dissolve polycarboxylate superplasticizer and HPMC in water and stir evenly to obtain a functional admixture solution. Add the functional admixture solution to the dry-mix powder and wet-mix for 7 min (room temperature 25℃). After mixing evenly, mold and cure the mixture. The curing conditions are: 20±2℃ and ≥95% humidity for 7–28 days.

[0052] Tests showed that the leaching concentrations of heavy metals Cu, Zn, and As after 28 days of curing were all below the limits set by the Integrated Wastewater Discharge Standard, with a fixation efficiency of >99%.

[0053] Example 2 is applicable to copper tailings with medium calcium content. A cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 100 parts by weight of PO 42.5 silicate cement, 80 parts by weight of slag powder, 20 parts by weight of quicklime, 30 parts by weight of desulfurized gypsum, 1.5 parts by weight of polycarboxylate superplasticizer (PC-311 type polycarboxylate superplasticizer), 0.3 parts by weight of HPMC, and 200 parts by weight of water (water-cement ratio = 0.87).

[0054] A method for using a cement-based copper tailings sand cementitious material, the method comprising the following steps: Weigh 1000 parts by weight of dry-based copper tailings (SiO2: 54%, CaO: 14%), dry the weighed dry-based copper tailings to a moisture content of <5%, and then crush them to a particle size of no more than 2 mm. Dry mix the copper tailings powder, cement, slag powder, quicklime and desulfurized gypsum for 3 min (room temperature 25℃) to obtain dry-mixed powder. Dissolve polycarboxylate superplasticizer and HPMC in water and stir evenly to obtain functional additives. Add the functional additives to the dry-mixed powder and wet mix for 6 min (room temperature 25℃). After mixing evenly, mold and cure. The curing conditions are: 7 to 28 days at a temperature of 20±2℃ and a humidity of ≥95%.

[0055] Tests showed that the leaching concentration of heavy metal Cu after 28 days of curing met the standards, and the shrinkage rate of the solidified body was reduced by 30% compared with conventional cement systems.

[0056] Example 3: Fluidized bed treatment of high water-cut tailings A cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 90 parts by weight of PO 42.5 silicate cement, 100 parts by weight of slag powder, 30 parts by weight of steel slag powder, 20 parts by weight of quicklime, 25 parts by weight of phosphogypsum, 2.2 parts by weight of polycarboxylate superplasticizer (PC-311 type polycarboxylate superplasticizer), 0.6 parts by weight of HPMC, and 20 parts by weight of water (for adjustment only).

[0057] A method for using a cement-based copper tailings sand cementitious material, the method comprising the following steps: Weigh 1300 parts by weight of wet tailings with a moisture content of 30% (equivalent to approximately 910 parts by weight of dry weight). Dry mix the weighed cement, slag powder, steel slag powder, quicklime, and phosphogypsum, and then add them to the wet tailings (the wet tailings are pre-crushed to a particle size not exceeding 2 mm). Mix evenly to obtain a wet tailings mixture. Dissolve polycarboxylate superplasticizer and HPMC in water and stir evenly to obtain a functional admixture. Add the functional admixture to the wet tailings mixture. Use a high-speed disperser or a dedicated mixing device, controlling the stirring linear speed at 10 m / s to 20 m / s (or the corresponding rotation speed of 300 r / min to 600 r / min, depending on the model of the mixer), and continue stirring for 3 min to 5 min until a uniform paste (slump approximately 22 cm) is formed. It can be directly pumped or cast, and then molded and cured. The curing conditions are: at a temperature of 20±2℃ and a humidity of ≥95%, curing for 7 to 28 days.

[0058] Tests showed that the cured body had a uniform structure and good impermeability. After 28 days of curing, the leaching concentrations of heavy metals Cu, Zn, and As were all below the limits set by the Integrated Wastewater Discharge Standard, with a fixation efficiency of >99%.

[0059] Comparative Example Comparative Example 1 The copper tailings cementitious material was used in a manner similar to that in Example 1, except that the copper tailings cementitious material was made from the following raw materials in parts by weight: 120 parts by weight of granulated blast furnace slag powder, 20 parts by weight of ultrafine steel slag powder, 30 parts by weight of gypsum, 30 parts by weight of PO 42.5 silicate cement, and 8 parts by weight of composite activator (of which the main components are 3 parts by weight of high-efficiency naphthalene-based water-reducing agent of sodium β-naphthalenesulfonate formaldehyde condensate, 1 part by weight of triethanolamine, and 4 parts by weight of lime).

[0060] Comparative Example 2 The copper tailings cementitious material was used in a manner similar to that in Example 1: The copper tailings cementitious material was prepared from the following raw materials in parts by weight: 120 parts by weight of granulated blast furnace slag powder, 20 parts by weight of ultrafine steel slag powder, 30 parts by weight of gypsum, 30 parts by weight of PO 42.5 silicate cement, 30 parts by weight of quicklime, 2.0 parts by weight of polycarboxylate superplasticizer, and 0.5 parts by weight of HPMC (hydroxypropyl methylcellulose ether).

[0061] Comparative Example 3 The copper tailings sand cementitious material was used in a manner similar to that in Example 1, except that no polycarboxylate superplasticizer was added.

[0062] Comparative Example 4 The copper tailings sand cementing material was used in a similar manner to that in Example 1, except that HPMC was not added.

[0063] Experimental Example Experiment Example 1 Mechanical Property Testing Unconfined compressive strength (unconfined compressive strength refers to the ultimate strength resisting axial pressure without lateral pressure), consolidation shrinkage rate, slump, and spread tests were conducted on the copper tailings cementitious materials described in Examples 1-3 and Comparative Examples 1-4, respectively. The testing standards for the unconfined compressive strength test were: "Standard for Geotechnical Testing Methods" (GB / T 50123-2019) and "Test Method for Strength of Cemented Backfill Body of Mine Tailings". The test results are shown in Table 1.

[0064] Table 1 Mechanical performance test results

[0065] As can be seen from Table 1, the unconfined compressive strength of the copper tailings sand solidified bodies formed in Examples 1-3 is 2.5-3.5 MPa after 7 days of curing and 4.0-4.5 MPa after 28 days of curing. This indicates that the copper tailings sand cementitious material described in this invention can be used to treat copper tailings to obtain solidified bodies with an unconfined compressive strength higher than 4.0 MPa, which can fully meet the engineering mechanical requirements of mine filling, roadbed reinforcement, etc., and realize the efficient utilization of solid waste.

[0066] Compared with Example 1, Comparative Examples 1 and 2 changed the raw materials and dosage of the cementitious material. After treating copper tailings with the cementitious materials described in Comparative Examples 1 and 2, the unconfined compressive strength after 7 days and 28 days of curing was significantly reduced. The above results show that the selection of raw materials and dosage of cementitious material have a significant impact on the unconfined compressive strength of copper tailings after curing. Only when the raw materials and dosage used are within the range defined by this invention can the unconfined compressive strength of copper tailings after treatment with cementitious material be improved.

[0067] Compared with Example 1, Comparative Example 3 did not add polycarboxylate superplasticizer. The unconfined compressive strength of the cementitious material prepared in Comparative Example 3 after treating copper tailings was significantly reduced after 7 days and 28 days of curing. The above results show that polycarboxylate superplasticizer has a significant impact on the unconfined compressive strength of oxidized copper tailings. Adding polycarboxylate superplasticizer to cementitious materials is beneficial to improving the unconfined compressive strength of copper tailings.

[0068] Compared with Example 1, Comparative Example 4 did not add HPMC. After the copper tailings were treated with the cementitious material described in Comparative Example 4, the unconfined compressive strength after 7 days and 28 days of curing was significantly reduced. The above results show that HPMC has a significant impact on the unconfined compressive strength of oxidized copper tailings. Adding HPMC to the cementitious material is beneficial to improving the unconfined compressive strength of copper tailings.

[0069] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A cement-based copper tailings geopolymer material, characterised in that, The cement-based copper tailings sand cementitious material comprises the following raw materials in parts by weight: The main gelling material consists of 70-110 parts by weight, an active activator of 70-190 parts by weight, a chemical stabilizer of 20-45 parts by weight, an alkalinity regulator of 15-35 parts by weight, and functional additives of 1.5-3.0 parts by weight.

2. The cement-based copper tailings geopolymer material according to claim 1, characterised in that, The cement-based copper tailings sand cementitious material comprises the following raw materials in parts by weight: The mixture contains 80-100 parts by weight of the main gelling material, 80-170 parts by weight of the active activator, 25-40 parts by weight of the chemical stabilizer, 20-30 parts by weight of the alkalinity regulator, 1.8-2.8 parts by weight of the functional additives, and 20-220 parts by weight of water.

3. The cement-based copper tailings sand cementitious material according to claim 1, characterized in that, The main cementitious material is silicate cement; The active activator is selected from one or more of granulated blast furnace slag powder, steel slag powder, metakaolin, and fly ash; and / or, The chemical stabilizer is selected from one or both of phosphogypsum and desulfurized gypsum; and / or, The alkalinity adjuster is quicklime; and / or... The functional additive is selected from one or more of polycarboxylate superplasticizers and hydroxypropyl methylcellulose ether.

4. The cement-based copper tailings sand cementitious material according to claim 3, characterized in that, The polycarboxylate superplasticizer is selected from one of the following: standard polycarboxylate superplasticizer, early-strength polycarboxylate superplasticizer, and retarded polycarboxylate superplasticizer.

5. The cement-based copper tailings geopolymer material according to claim 2, characterised in that, The cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 80 parts by weight of silicate cement, 120 parts by weight of slag powder, 50 parts by weight of steel slag powder, 30 parts by weight of quicklime, 40 parts by weight of phosphogypsum, 2.0 parts by weight of polycarboxylate superplasticizer, 0.5 parts by weight of hydroxypropyl methylcellulose ether, and 220 parts by weight of water.

6. The cement-based copper tailings geopolymer material according to claim 2, characterised in that, The cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 100 parts by weight of silicate cement, 80 parts by weight of slag powder, 20 parts by weight of quicklime, 30 parts by weight of desulfurized gypsum, 1.5 parts by weight of polycarboxylate superplasticizer, 0.3 parts by weight of hydroxypropyl methylcellulose ether, and 200 parts by weight of water.

7. The cement-based copper tailings sand cementitious material according to claim 2, characterized in that, The cement-based copper tailings sand cementitious material is prepared from the following raw materials in parts by weight: 90 parts by weight of silicate cement, 100 parts by weight of slag powder, 30 parts by weight of steel slag powder, 20 parts by weight of quicklime, 25 parts by weight of phosphogypsum, 2.2 parts by weight of polycarboxylate superplasticizer, 0.6 parts by weight of hydroxypropyl methylcellulose ether, and 20 parts by weight of water.

8. A method of using the cement-based copper tailings sand cementitious material according to any one of claims 1 to 7, characterized in that, The method of use includes the following steps: Step 1: Crush the copper tailings to obtain copper tailings powder. Mix the copper tailings powder, cementing main material, active activator, alkalinity regulator and chemical stabilizer to obtain copper tailings mixture. Step 2: Add the functional additive to water and mix well to obtain a functional additive solution. Add the functional additive solution to the copper tailings mixture, stir well, and then shape and cure.

9. The method of use according to claim 8, characterized in that, In step 1, The copper tailings were crushed to a particle size of ≤3 mm. The mixing temperature is 20–30°C, and the mixing time is 2–5 min.

10. The method of use according to claim 8, characterized in that, In step 2, The stirring temperature is 20–30°C, and the stirring time is 5–8 minutes.

Citation Information

Patent Citations

  • A filling gelling material suitable for low-concentration ultrafine copper polymetallic tailings and a preparation method thereof

    CN119735417A